2001
DOI: 10.4049/jimmunol.166.2.1049
|View full text |Cite
|
Sign up to set email alerts
|

Histoplasma capsulatumYeasts Are Phagocytosed Via Very Late Antigen-5, Killed, and Processed for Antigen Presentation by Human Dendritic Cells

Abstract: Histoplasma capsulatum (Hc) is a facultative, intracellular parasite of world-wide importance. As the induction of cell-mediated immunity to Hc is of critical importance in host defense, we sought to determine whether dendritic cells (DC) could function as a primary APC for this pathogenic fungus. DC obtained by culture of human monocytes in the presence of GM-CSF and IL-4 phagocytosed Hc yeasts in a time-dependent manner. Upon ingestion, the intracellular growth of yeasts within DC was completely inhibited co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 104 publications
(112 citation statements)
references
References 59 publications
7
104
0
1
Order By: Relevance
“…Clonal analysis of MART1-specific CTLs has shown that MART1/T-cell receptor interactions are tightly restricted to HLA-A2, 37 and a recent study found that mature human MoDCs do not efficiently process and present the MART1 [27][28][29][30][31][32][33][34][35] epitope from whole MART1 due to the presence of the immunoproteasome, 38 suggesting that delivery of some whole proteins, including MART1, may not be an effective method of antigen delivery to DCs. Immature DCs express both the standard proteasome and immunoproteasomes.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Clonal analysis of MART1-specific CTLs has shown that MART1/T-cell receptor interactions are tightly restricted to HLA-A2, 37 and a recent study found that mature human MoDCs do not efficiently process and present the MART1 [27][28][29][30][31][32][33][34][35] epitope from whole MART1 due to the presence of the immunoproteasome, 38 suggesting that delivery of some whole proteins, including MART1, may not be an effective method of antigen delivery to DCs. Immature DCs express both the standard proteasome and immunoproteasomes.…”
Section: Discussionmentioning
confidence: 99%
“…The presentation of the MART1 [27][28][29][30][31][32][33][34][35] epitope to the HLA-A2 molecule on MoDCs was examined by measuring IFN-␥ production by the CD8 ϩ T cells within the MART1-specific CTL population in response to E. coli-infected DCs. Immature DCs (10 5 cells, either HLA-matched and HLA-mismatched) were incubated with E. coli (at a ratio of 10 bacteria per DC for 16 hr) or pulsed with control peptides (10 g/ml, 1 hr).…”
Section: Antigen Presentation Assaysmentioning
confidence: 99%
See 3 more Smart Citations